Utilization of Sago Liquid Waste Organic Fertilizer as a Culture Medium for Chlorella sp. - Irwan Effendi; Mega Novia Putri; Ulfi Laili Astika; Ronal Kurniawan (Jurnal Natur Indonesia, 2023)
Chlorella sp. is a microalga that can grow and develop in wastewater media, including sago liquid waste that is not utilized and becomes a pollution material. This study aims to determine the utilization of sago liquid waste organic fertilizer on the growth of Chlorella sp. This research was conducted in February 2023 at the Marine Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Riau University. The method used was the experimental method, by applying a complete randomized design (CRD) with four treatments and three replicates. The treatments were as follows: T0 (control), T1 (150 ml sago liquid waste), T2 (200 ml), and T3 (250 ml). The initial density of Chlorella sp. was 250 x103 cells/ml, and cell abundance observations were made for 14 days. The parameters observed were cell abundance, specific growth rate, and water quality (temperature and pH). The results showed that the utilization of sago liquid waste affected the abundance of Chlorella sp. 150 ml concentration and gave the best results on cell abundance of 233.33 x103 cells/ml with the peak population occurring on day 9. Water quality during the study was still in the normal range and can be tolerated for the growth of Chlorella sp, namely temperature ranging from 26-31o C and pH 6.2-8.0.